Factors Influencing Girls Education Development in Hodan- District- Somalia - Mohamed, Abdirahman Sheik Mohamud; Nekesa, Grace (International Journal For Research In Educational Studies, 2018)
The purpose of the study was to investigate the effects of economic, social, cultural, political factors on girls’ education development in Hodan district. The research design of the study was descriptive research design. The target population was 125. Slovens formula was used to arrive at sample of 96. Stratified random sampling method was used. Structured questionnaire was used to collect data. The data was coded and analyzed and researcher used statistical package for social sciences (SPSS) Version 21 for data analysis. Correlation, regression, ANOVA and model summary was generated and data was presented in form of tables. The research findings show that community’s attitude towards girls education development is still very low. The study found out that there was a positive and significant relationship between the independent and the dependent variable. The study concluded that all independent variables (economic, cultural factors, social and economic factors has statistically significant influence on dependant variable (Girls education development). Majority of the respondents recommended that awareness be created to all stakeholders on the importance of girl child education. The researcher recommendeda sensitization program be conducted on the significance of the girl child education to the community. It is also recommended that government should enforce laws to deal with early and forced marriages. It is also recommended that government formulate policies that address gender imbalances in acquisition of education among communities.